2019
DOI: 10.1111/1750-3841.14465
|View full text |Cite
|
Sign up to set email alerts
|

Response to Acid Adaptation in Salmonella enterica Serovar Enteritidis

Abstract: Acid adaptation in Salmonella Enteritidis was characterized by phenotypic and gene‐expression analyses. S. Enteritidis cells at log‐phase and stationary‐phase were kept at pH 4.5 to 6.0 for 1 to 4 hours. All treatments induced various levels of acid tolerance response that were dependent on pH, exposure time and growth phase. This acid adaptation resulted in tolerance to 50 °C and 8% NaCl regardless of the growth phase. However, the tolerance of log‐phase and stationary‐phase cells to low temperatures (4 and –… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…This inorganic acid was used because it is completely dissociated in aqueous environments and therefore itself is not toxic for the cells [ 29 ]. In line with previous reports, adaptation to moderate pH values (4.0–5.5) protected cells against subsequent acid exposure, with higher resistance observed at the lower pH values (4.0 and 4.5) [ 30 33 ]. Nonetheless, the pH values required for the induction of acid resistance in pH adapted cells were lower compared to the milder pH values (5.5–6.0) required in the presence of acetic acid.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This inorganic acid was used because it is completely dissociated in aqueous environments and therefore itself is not toxic for the cells [ 29 ]. In line with previous reports, adaptation to moderate pH values (4.0–5.5) protected cells against subsequent acid exposure, with higher resistance observed at the lower pH values (4.0 and 4.5) [ 30 33 ]. Nonetheless, the pH values required for the induction of acid resistance in pH adapted cells were lower compared to the milder pH values (5.5–6.0) required in the presence of acetic acid.…”
Section: Discussionsupporting
confidence: 91%
“…Shen, Yu and Chou [50] reported that whereas no differences were observed between acid adapted and non-adapted cells of S. Typhimurium inoculated in skim milk and treated fermented milk stored at 37˚C, acid adaptation, in addition to promoting acid resistance, decreased the susceptibility of the pathogen to refrigeration (5˚C). Nonetheless, it is not the first time that the effects of acid adaptation are counteracted by subsequent stressors, increasing the sensitivity of acid adapted cells to lethal stresses compared to their non-adapted counterparts [33,51,52].…”
Section: Plos Onementioning
confidence: 99%
“…CspA , a gene encoding cold shock protein, was up-regulated by 7.29 times in the liquid-state fermented cells compared with the solid-state fermented cells. This gene has been reported to be involved in the response to cold stress and acid stress [ 70 ]. Gene rimP encoding ribosome maturation factor was up-regulated by 2.58 times.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the multitude of genes involved in each stress response, it is difficult to single‐out a specific direct response. In previous experiments, it was found that exposure to one stress primes tolerance to other stresses (Stackhouse et al., 2012; Vorob'eva, 2004; Ye et al., 2019). In this study, the bacteria are exposed to either one, some, or all of the stresses.…”
Section: Discussionmentioning
confidence: 96%